Congenital Defects in Actin Dynamics of Germinal Center B Cells - He, Minghui; Westerberg, Lisa S. (Frontiers in Immunology, 2019)
The germinal center (GC) is a transient structure formed during the adaptive immune response that leads to antibody affinity maturation and serological memory. Recent works using two-photon microscopy reveals that the GC is a highly dynamic structure and GC B cells are highly motile. An efficient selection of high affinity B cells clones within the GC crucially relies on the interplay of proliferation, genome editing, cell-cell interaction, and migration. All these processes require actin cytoskeleton rearrangement to be well coordinated. Dysregulated actin dynamics may impede on multiple stages during B cell affinity maturation, which could lead to aberrant GC response and result in autoimmunity and B cell malignancy. This review mainly focuses on the recent works that investigate the role of actin regulators during the GC response.